Far from the tree - Benway, Robin (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2017)
Grace, an only child who was adopted at birth, discovers that she is the middle child in her biological family after she gives up her own child for adoption, and she struggles to bond with her stoic older brother and outspoken younger sister.
Grace, an only child who was adopted at birth, discovers that she is the middle child in her biological family after she gives up her own child for adoption, and she struggles to find belonging as she tries to bond with her stoic older brother and outspoken younger sister.
Keywords: Adopted children -- Fiction; Middle-born children -- Fiction; Brothers and sisters -- Fiction; Teenage pregnancy -- Fiction; Family secrets -- Fiction; Family life -- Fiction; Adopted children -- Fiction; Birth order -- Fiction; Siblings -- Fiction; Teenage pregnancy -- Fiction; Secrecy -- Fiction; Family life -- Fiction